Effects of dot density, patch size and contrast on the upper spatial limit for direction discrimination in random-dot kinematograms - Eagle, R; Rogers, B (Elsevier, 1997)
Two-frame random-dot kinematograms (RDKs) of different dot density, area and contrast were used to study the spatial properties of the human visual motion system. It was found that the maximum spatial displacement at which observers could reliably discriminate the direction of motion (dmax) increased gradually by a factor of up to 6.4 as dot density was decreased from 50 to 0.025% for high Michelson contrast (0.997) stimuli. As stimulus area was reduced from 645 deg2, this trend gradually disappeared so that by a stimulus area of 2.56 deg2, there was no effect of density upon dmax. A further experiment investigated the effects of reducing Michelson contrast from 0.77 to 0.2 on dmax over this same range of dot densities. It was found that at the highest densities, dmax declined as contrast was reduced. Furthermore, for contrasts at and below 0.4, dmax was invariant of density over the range 50-5%. These results can be accounted for by the fact that both reducing contrast, while keeping density fixed, and reducing density, while maintaining a fixed high contrast, reduce the stimulus mean luminance. For all contrasts, decreasing density below 5% led to an increase in dmax. However, the rate of this increase was slower for the lower contrast stimuli. A two-stage model based on bandpass filtering followed by an informationally limited motion detection stage is proposed and shown to provide a good account of these data.